Status of Agricultural Trade in Asia Pacific Region: A Recent Study - P. Soumya; R. A. Yeledhalli (Current Topics in Agricultural Sciences Vol. 2, 2021)
The present study was carried out to assess the growth rate of agricultural exports and imports in major countries in Asia Pacific region along with entire Asia Pacific region. Data for a period of 27 years i.e., from 1992 to 2018 is considered for analysis. Among major countries, compound annual growth rate for export of agricultural commodities in terms of value is highest for Indonesia (10.28%) followed by India (9.52%), China (8.60%), Thailand (6.30%) and Australia (4.68%). The agricultural commodity export for major exporting countries in Asia Pacific in terms of value showed an increasing trend due to increase in unit value of commodities. The agricultural exports from Asia Pacific region and the world showed positive and significant annual growth rate of 7.90 per cent and 7.09 per cent, respectively. The major importing countries India, China, Indonesia, Republic of Korea and Japan showed positive and significant growth rate of 12.92, 12.89, 8.64, 5.92 and 1.78 per cent per annum respectively. There is increasing trend in agricultural commodity imports in terms of value due to increase in income, changing life style of people and changing commodity prices. And also, there is increasing trend in import of agricultural commodities to Asia Pacific region (7.29%) and world (6.94%). In case of Asia Pacific agricultural exports as well as imports, the share of Animal and Fibre products decreased whereas share of Vegetable and Food products increased gradually over the study period. The growth rate of Vegetable products is 9.33 and 9.29% in case of exports and imports, respectively. The growth rate of both agricultural exports and imports is increasing for entire Asia Pacific region due to increasing share of Vegetable products. There is need for reforms which must focus on liberalizing logistics, facilitating adoption of modern information and communication technologies promoting competition among service providers and improving access to credit and trade finance.